PENGEMBANGAN PENILAIAN MATERIAL MECHANICAL, ELECTRICAL, DAN PLUMBING RAMAH LINGKUNGAN - Deni Setiawan; Michael Kristianto Marbun (Jurnal Teknik Sipil, 2021)
Implementation of "Green Building" in construction is the responsibility of all parties involved in the construction project. The Office of the Federal Environment Executive (OFEE) defines green buildings or green buildings as “the practice of increasing the efficiency by which buildings and their sites use energy, air, and materials, and reducing the impact of buildings on health and the environment, through better siting, design work. construction, operation and removal - maintenance of the complete building life cycle. (Kubba, 2017). At the planning and implementation stage of a construction project the selection of building materials or materials must be precise but also efficient. The concept of eco-efficiency was introduced in 1991 by the World Business Council for Sustainable Development - WBCSD and includes “the development of competitively priced products and services that meet the needs of the quality of human life, while progressively reducing impact on the environment and consumption of raw materials throughout the life cycle accordingly. with the capacity that is on planet earth. "This concept means producing more products with less resources and less waste, and therefore this concept has less impact on the environment. Then it is necessary to assess all the environmental impacts caused by the extraction of raw materials from the start of the material being given (cradle) to the end of its service life (tomb). The research objective is to develop environmentally friendly materials for problem solving materials, electricity and plumbing. The results of the analysis show that the mechanical, electrical, and piping materials used in the Maranatha Sport Center project have not met the 7 overall environmentally friendly criteria for the material-life-span stage, however, each material used has the main green criteria that have been self-declared by each. -Each material manufacturer.